Analisis Pengaruh Budaya Kerja dan Pengembangan Karir Terhadap Produktivitas Kerja Karyawan Pada PT. Metindo Era Sakti - Rakhmat; Nurwati (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
Metindo Era Sakti (MES) is a company engaged in the automotive sector that requires an increase in good human resources. However, in the last 2 years PT. MES did not show exponential increase in production volume, even in several semesters it experienced a decrease in production. In the initial observation, HRD PT. MES conveys information about work culture and career development as the cause of the decrease in the number of production. The problems faced by PT.MES related to employees include but are not limited to aspects of the inability of employees to complete work, ineffective work culture, unclear job descriptions and low work ethic, these problems cause decreased employee productivity which ultimately affect the production side of PT. MES. The purpose of this study is to find out how much influence work culture and career development have on employee work productivity at PT. Metindo Era Sakti. Based on the research results, it can be concluded that Work Culture (X1) and Career Development (X2) have an influence on Productivity (Y).